2018
DOI: 10.7554/elife.33321
|View full text |Cite
|
Sign up to set email alerts
|

Stomach-brain synchrony reveals a novel, delayed-connectivity resting-state network in humans

Abstract: Resting-state networks offer a unique window into the brain’s functional architecture, but their characterization remains limited to instantaneous connectivity thus far. Here, we describe a novel resting-state network based on the delayed connectivity between the brain and the slow electrical rhythm (0.05 Hz) generated in the stomach. The gastric network cuts across classical resting-state networks with partial overlap with autonomic regulation areas. This network is composed of regions with convergent functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
205
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(218 citation statements)
references
References 87 publications
13
205
0
Order By: Relevance
“…Rebollo et al . () extended this finding in a BOLD study and showed that a brain network (termed gastric network) is phase synchronized with the gastric basal rhythm. Within this gastric network, approximately 15% of the BOLD variance is explained by gastric phase.…”
Section: Coupling Between Body and Brain Body Oscillationsmentioning
confidence: 74%
“…Rebollo et al . () extended this finding in a BOLD study and showed that a brain network (termed gastric network) is phase synchronized with the gastric basal rhythm. Within this gastric network, approximately 15% of the BOLD variance is explained by gastric phase.…”
Section: Coupling Between Body and Brain Body Oscillationsmentioning
confidence: 74%
“…Participants were then asked to lie down on a bed. To measure the electrogastrogram (EGG), the skin above the abdomen was cleaned and six (four EGG electrodes, reference and ground electrode) standard electrocardiogram electrodes with solid gel (3M red dot) were applied according to the placement described in [1]. The electrodes were connected to a BrainAmp DC (BrainProducts, Gilching, Germany) EEG recording system and electrodes were left in place for the second session.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Interestingly, recent studies are starting to unveil relationships between oscillatory activity produced by different organ systems. For instance, Tallon-Baudry and collaborators have shown that ascending signals from the heart and gastrointestinal tract modulate brain dynamics and affect perception, emotion and cognition [10][11][12][13]. In particular, the EEG alpha rhythm was shown to be modulated by the phase of the gastric cycle [7].…”
Section: Introductionmentioning
confidence: 99%